Malnutrition in Elderly Patients with Chronic Kidney Disease—The Role of Albuminuria - Diana Moldovan; Ina Kacso; Lucreția Avram; Cosmina Bondor; Crina Rusu; Alina Potra; Dacian Tirinescu; Maria Ticala; Ariana Condor; Dana Crisan; Valer Donca (Life)
Background: The global population is rapidly aging, and an epidemic increase in chronic kidney disease (CKD) has been reported. As the presence of malnutrition in elderly CKD patients can pose serious health problems, the aim of our study was to identify, using different assessment tools, the relationship between nutrition with kidney function and albuminuria in elderly patients. Methods: The study included 793 hospitalized patients aged 65 years and older. A comprehensive assessment of nutritional status and renal involvement was performed, and the relationship between malnutrition and kidney issues was tested. Results: CKD was highly prevalent in our geriatric population, with 39.84% having CKD G3a–5. Malnutrition, determined according to the Mini Nutritional Assessment (MNA) score, was identified in 34.6% of patients. With an increase in albuminuria, we observed worse nutrition indicators: low serum albumin; lower body fat (p = 0.002) and visceral fat (p = 0.001), assessed via bioimpedance; and lower MNA (p = 0.04) and geriatric nutritional risk index (GNRI) (p = 0.002) scores. Elderly patients with CKD G3a–5 had lower HDL-cholesterol (p < 0.001), higher triglycerides (p < 0.001), lower albumin (p = 0.011), and a lower MNA score (p = 0.001). Conclusions: Malnutrition was found to be common and more severe with increased albuminuria and decreased eGFR. Our study sheds light on a novel relationship between malnutrition, albuminuria, and renal function in a geriatric population.